${a^{1/3}} + {a^{ - 1/3}}$ નો સંમેય કારક અવયવ મેળવો.
${a^{1/3}} - {a^{ - 1/3}}$
${a^{2/3}} + {a^{ - 2/3}}$
${a^{2/3}} - {a^{ - 2/3}}$
${a^{2/3}} + {a^{ - 2/3}} - 1$
જો $x + \sqrt {({x^2} + 1)} = a,$ તો $x =$
${{15} \over {\sqrt {10} + \sqrt {20} + \sqrt {40} - \sqrt 5 - \sqrt {80} }} = . . . $
જો ${7 \over {{2^{1/2}} + {2^{1/4}} + 1}}$$ = A + B{.2^{1/4}} + C{.2^{1/2}} + D{.2^{3/4}}$, તો $A+B+C+D= . . .$
જો $x = 3 - \sqrt {5,} $ તો ${{\sqrt x } \over {\sqrt 2 + \sqrt {(3x - 2)} }} = $
જો ${x^y} = {y^x},$ તો ${(x/y)^{(x/y)}} = {x^{(x/y) - k}},$ કે જ્યાં $k = . . . . $